Mechanical breathing in organic electrochromics - Xiaokang Wang; Ke Chen; Luize Scalco de Vasconcelos; Jiazhi He; Yung C. Shin; Jianguo Mei; Kejie Zhao (Nature Communications, 2020)
Though organic electrochromic devices are promising for various applications, their performance is limited by a cyclic change in volume of the material over time. Here, the authors study mechanical breathing in a model polymer and provide rules for the design of new mechanically-reliable materials.